Intra-subject variability of 5 km time trial performance completed by competitive trained runners - Fisher, J.; Clark, T.; Newman-Judd, K.; Arnold, J.; Steele, J. (Journal of Human Kinetics, 2017)
Time-trials represent an ecologically valid approach to assessment of endurance performance. Such information is useful in the application of testing protocols and estimation of sample sizes required for research/magnitude based inference methods. The present study aimed to investigate the intra-subject variability of 5 km time-trial running performance in trained runners. Six competitive trained male runners (age = 33.8 ± 10.1 years; stature = 1.78 ± 0.01 m; body mass = 69.0 ± 10.4 kg, V.O2max = 62.6 ± 11.0 ml·kg·min-1) completed an incremental exercise test to volitional exhaustion followed by 5 x 5 km time-trials (including a familiarisation trial), individually spaced by 48 hours. The time taken to complete each trial, heart rate, rating of perceived exertion and speed were all assessed. Intra-subject absolute standard error of measurement and the coefficient of variance were calculated for time-trial variables in addition to the intra-class correlation coefficient for time taken to complete the time-trial. For the primary measure time, results showed a coefficient of variation score across all participants of 1.5 ± 0.59% with an intra-class correlation coefficient score of 0.990. Heart rate, rating of perceived exertion and speed data showed a variance range between 0.8 and 3.05%. It was concluded that when compared with related research, there was observed low intra-subject variability in trained runners over a 5 km distance. This supports the use of this protocol for 5 km time-trial performance for assessment of nutritional strategies, ergogenic aids or training interventions on endurance running performance.